PUBLIC TRANSPORTATION POLICY ANALYSIS TO REDUCE PRIVATE VEHICLE DEPENDENCE IN PANGKALPINANG CITY AND BANGKA REGENCY - Frans Tory Damara Pradipta (Institut Riset dan Pengembangan Indonesia, 2026)
The increasing number of private vehicles in Pangkalpinang City and Bangka Regency has contributed to traffic congestion, mobility inefficiency, and growing dependence on individual transportation. The absence of an integrated public transportation system has encouraged residents to rely mainly on motorcycles and private cars for daily activities. This study aims to analyze public transportation policy development as an alternative strategy to reduce private vehicle dependence and support sustainable urban mobility. The research applies a qualitative approach through literature review and analysis of regional statistical data, policy documents, and relevant academic studies on public transportation governance. The findings indicate that the growth of private vehicles is not balanced by the availability of reliable public transport services, resulting in increased traffic density in urban activity centers and inter-regional routes. Policy direction emphasizing accessible, integrated, and service-oriented public transportation is considered essential, including the development of city transit systems, urban feeder transport, and strengthened local government coordination. The study concludes that public transportation development can become a strategic policy instrument to improve mobility efficiency while reducing congestion risks in Pangkalpinang City and Bangka Regency.